PENERAPAN MODEL PEMBELAJARAN PENEMUAN TERBIMBING UNTUK MENCAPAI KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN LAJU REAKSI DI KELAS XI MAN 1 PEKANBARU - Febriana Susanti Susanti; Betty Holiwarni Holiwarni; Roza Linda Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Research on the application of Guided Discovery learning model aims to achieve student’s mastery learning on the topic of the reaction rate in class XI Science MAN 1 Pekanbaru. This research used one shot-study case design. Time of data retrieval from the date November 11rd – 27rd 2014. The sample was selected from the four existing classes, obtained class XI Science 1. Data analysis technique used the percentage calculation of mastery learning classical. Based on the results of data processing obtained mastery learning classical of  knowledge competency is 90,625%, attitude competency is 100% and skill competency is 100%, means that the application of Guided Discovery learning model can achieve student’s mastery learning on the topic of the reaction rate in class XI Science 1 MAN 1 Pekanbaru. Keywords :      Guided Discovery, Mastery Learning, Reaction Rate